Systemic Regeneration and Circular Society - Rufino, Annamaria (Italian Sociological Review, 2020)
The spread of the pandemic represented the upheaval of the order constituted (status quo), as the most evident data. It’s possible to think of the dynamics within the EU, the relationship between the various political systems, taken as single entities and in their inter-institutional relationships. The Coronavirus also called into question strategies that seemed politically well established, for example the ways the US electoral campaigns are conducted and shed a light on political dynamics and practices that usually are less talked about, if not in a detrimental manner, such as the polices carried out by political representatives such as Mr Erdoğan and Mr. Orbán. It has unbalanced economic-financial domains, which imposed themselves as unassailable, as it has been the case for China. But, not least, the pandemic has disarticulated social and relational models, in every country of the world. Not even the First and the Second World Wars had achieved that. Everything, inevitably, will result in a rethinking of the regulatory and decision-making processes; likewise, the ‘way’ of life and the ways relationships are built will undergo a ‘restoration’ process based on the redefinition of needs, expectations and, above all, desires. Those will have to be identified according to a new series of elementary and essential rights to be guaranteed to everyone.